2004
DOI: 10.1007/s10616-005-2105-z
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the medium perfusion rate in a packed-bed bioreactor charged with CHO cells

Abstract: In the present study, the optimal medium perfusion rate to be used for the continuous culture of a recombinant CHO cell line in a packed-bed bioreactor made of Fibra-Cel Ò disk carriers was determined. A first-generation process had originally been designed with a high perfusion rate, in order to rapidly produce material for pre-clinical and early clinical trials. It was originally operated with a perfusion of 2.6 vvd during production phase in order to supply the high cell density ($2.5 · 10 7 cell ml À1 of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 30 publications
(28 reference statements)
0
8
0
Order By: Relevance
“…In order to reduce the COGS of a sub-optimal process developed to produce the material for early clinical trial, Meuwly et al (2004) studied the effect of decreasing the perfusion rate of a CHO cell-based process in packed-bed bioreactor. He observed that a 25 % reduction compared to the original level was satisfying for the yield and quality of POI while 50 % reduction caused a 30 % productivity loss however without alteration of the quality.…”
Section: Perfusion Rate Strategy Based On Csprmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to reduce the COGS of a sub-optimal process developed to produce the material for early clinical trial, Meuwly et al (2004) studied the effect of decreasing the perfusion rate of a CHO cell-based process in packed-bed bioreactor. He observed that a 25 % reduction compared to the original level was satisfying for the yield and quality of POI while 50 % reduction caused a 30 % productivity loss however without alteration of the quality.…”
Section: Perfusion Rate Strategy Based On Csprmentioning
confidence: 99%
“…A sub-optimal process, requiring limited efforts, can be acceptable for a rapid POI production for Discovery/Research, in the case of a process developed for pre-clinical and early clinical phases under hard time constraints. The process can then be further optimized in preparation for the commercial phase (Meuwly et al 2004). More work will be needed when Fig.…”
Section: Introductionmentioning
confidence: 99%
“…While major glycosylation changes and optimizations are generally effectuated at the genome level, some bioprocess parameters can also influence the structure and homogeneity of the carbohydrate moiety, both during cultivation and purification (Goochee and Monica, 1990;Jenkins et al, 1996). The effect on glycosylation of cultivation parameters such as glucose starvation, pH, perfusion rate, temperature or batch length have been investigated in details for mammalian cells (Andersen et al, 2000;Meuwly et al, 2004;Yuen et al, 2003). Similar studies on product quality were performed with P. pastoris, but rather than investigating glycosylation, they concentrated on protein activity or level of aggregation.…”
Section: Introductionmentioning
confidence: 99%
“…Development of biotechnological processes in general, with a special emphasis on animal cell culture, is aimed at defining bioprocess solutions that warrant high volumetric productivity, batch-to-batch consistency and homogenous product quality at low costs [ 179 ]. Walther et al [ 180 ] have recognized two major needs for future biomanufacturing: increased flexibility and reduced cost of goods.…”
Section: General Aspects Of Bioreactors For Proliferation and Differe...mentioning
confidence: 99%